2007
DOI: 10.1111/j.1465-7287.2007.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Americans Addicted to Baseball? An Empirical Analysis of Fandom in Korea and the United States

Abstract: "Theories of rational addiction posit that certain habit-forming goods-characterized by an increasing marginal utility of consumption-generate predictable dynamic patterns of consumer behavior. It has been suggested that attendance at sporting events represents an example of such a good, as evidenced by the pricing strategies of commercial sports interests. In this essay, we provide new evidence in support of rational addiction for the case of Major League Baseball but fail to find such support in data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Lagwin% is the winning percentage of the team during the previous season. This variable is utilized to control for fan expectations early in the season, but may also pick up any habitual nature of fans (Lee and Smith, 2008). Stadiumnew is inserted in the model to control for the increased demand attributable to the novelty effect of new stadiums and is an indicator variable for whether a team's home stadium was in its first year of use.…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…Lagwin% is the winning percentage of the team during the previous season. This variable is utilized to control for fan expectations early in the season, but may also pick up any habitual nature of fans (Lee and Smith, 2008). Stadiumnew is inserted in the model to control for the increased demand attributable to the novelty effect of new stadiums and is an indicator variable for whether a team's home stadium was in its first year of use.…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…Thus, habit formation in sports game attendance is crucial for the sports business. Lee and Smith () examined habitual consumption of KBO and MLB using two separate panel datasets: 1982–2002 for KBO and 1991–2000 for MLB. They found empirical evidence for economically and statistically significant habit formation in MLB attendance, but no significant habitual attendance in KBO.…”
Section: Fan Loyalty and Habitual Attendancementioning
confidence: 99%
“…The Japanese Nippon Professional Baseball League (NPB) and the Korea Baseball Organization (KBO) are now the second and third largest professional baseball leagues in the world in terms of revenue‐generating ability, after Major League Baseball (MLB). Considerable research has focused on these two Asian baseball leagues (La Croix & Kawaura, ; Lee, , ; Lee & Smith, ; Yamamura, ; Leeds & Sakata, ; Fort et al ., ; Humphreys & Watanabe, ). Scholars have analyzed various issues.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive literature on habitual formation in consumption (Becker and Murphy, 1988;Becker et al, 1990Becker et al, , 1991Becker et al, , 1994Dynan, 2000;Ahn and Lee, 2007;Lee and Smith, 2008). Becker and Murphy (1988) studied the long-run and short-run effects of habit persistence on addictive consumption goods.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the consumption of baseball games is strongly habit-forming. In addition, Lee and Smith (2008) applied the model of Ahn and Lee (2007) and compared the Korean baseball league with MLB. Unlike MLB, the Korean baseball league does not possess a property of habitual attending.…”
Section: Introductionmentioning
confidence: 99%